INVESTIGATING STUDENTS’ MONITORING STRATEGIES IN LISTENING COMPREHENSION III OF ENGLISH DEPARTMENT AT STAIN BATUSANGKAR - ELFI ELFI (Ta'dib, 2015)
One of the strategies of metacognitive introduced by the listening lecturers in listening comprehension III at STAIN Batusangkar is monitoring strategies. It is assumed that these strategies can help students solve their problem in listening comprehension in order to comprehend oral text correctly. The purposes of this research are to investigate what kind of students’ monitoring strategies are used and how they applied it in listening comprehension.The research method was descriptive qualitative.The participants of the research were English students who took listening comprehension III. 91 students were involved as the respondents to answer the questionnaire, and 12 students among them were selected to be interviewed using snowball sampling technique. The data of the research were collected by using questionnaire, interview, and observation. After analizing the data, it was found that most of students used monitoring strategies. These strategies include as: ask if it makes sense, selected attend, deduction, personalizing or contextualizing, taking note, using imagery, self talk, and cooperative strategy. They had applied these strategies in many ways but some of the them did not do it properly. Based on these findings, It can be concluded thatmonitoring strategies used by the students in listening comprehension need to enhance into the correct ways to get better comprehension in listening.Key words: Investigating, Metacognitive strategies, Monitoring strategies, Listening Comprehension